Electrochemical Devices
By arranging a nanofiber porous layer on the surface of the electrode plate of the lithium-ion battery, and forming a polymer layer and an inorganic compound layer on it, the problems of poor uniformity, low porosity and weak adhesion of traditional isolation membranes are solved. Better injection performance and safety are achieved while increasing energy density.
Patent Information
- Application Number
- CN202080094476.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-03-27
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2040-03-27
AI Technical Summary
The existing technology of not installing ordinary isolation films between the positive and negative electrodes of lithium-ion batteries has problems such as poor polymer layer uniformity, low porosity, large solvent use, and weak adhesiveness of ceramic layers, resulting in deterioration in the rate performance of lithium-ion batteries and Safety hazards.
A porous layer is provided on the surface of the electrode plate. The porous layer contains nanofibers, and a polymer layer and an inorganic compound layer are formed on it to replace the traditional isolation membrane.
By increasing the porosity, adhesion and mechanical strength of the isolation layer, the liquid injection performance and safety of lithium-ion batteries are significantly improved, while the energy density is increased.
Smart Images

Figure CN115380430B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical devices, and in particular to a lithium-ion battery. Background Art
[0002] Lithium-ion batteries have many advantages such as high energy density, long cycle life, high nominal voltage (>3.7V), and low self-discharge rate, and are widely used in the field of consumer electronics. With the rapid development of electric vehicles and mobile electronic devices in recent years, people have higher and higher requirements for the energy density, safety, and cycle performance of lithium-ion batteries, and are looking forward to the emergence of new lithium-ion batteries with comprehensive performance improvements. Among them, setting an isolation layer between the positive and negative electrodes of lithium-ion batteries instead of the traditional ordinary isolation film is a new technology that has attracted much attention.
[0003] The existing technology of lithium-ion batteries without ordinary separators between the positive and negative electrodes is mainly achieved by preparing a polymer layer and (or) ceramic layer on the surface of the electrode plate by a scraping method. Its main disadvantages are as follows: the uniformity of the polymer layer is poor, and there are large differences in weight and thickness per unit area; the polymer layer has a low porosity, which will block the lithium ion transmission path on the surface of the electrode plate, causing serious deterioration of the rate performance of the lithium-ion battery; a large amount of solvent is required during the scraping method preparation process, which will damage the active substances and adhesives on the surface of the electrode plate; the ceramic layer has a weak bonding force with the electrode plate, which will cause safety hazards. Therefore, it is necessary to develop a new material or structure to replace the traditional separator. Summary of the invention
[0004] The purpose of the present application is to provide an electrochemical device that does not require the use of a traditional isolation membrane.
[0005] The first aspect of the present application provides an electrochemical device, including an electrode plate and an isolation layer formed on the surface of the electrode plate, wherein the isolation layer includes a porous layer formed on the surface of the electrode plate; the porous layer includes nanofibers, and the electrolyte injection property of the isolation layer is less than 15 seconds.
[0006] In some embodiments of the first aspect of the present application, the isolation layer has at least one of the following features:
[0007] (a) When the thickness of the isolation layer is converted to 20 μm, the air permeability is 5 s / 100 cm 3 ~400s / 100cm 3 ;
[0008] (b) the porosity of the isolation layer is 30% to 95%;
[0009] (c) the average pore size of the porous layer is 20 nm to 10 μm;
[0010] (d) The thickness of the isolation layer is 1 μm to 20 μm.
[0011] In some embodiments of the first aspect of the present application, the diameter of the nanofiber is 0.1 nm to 2 μm.
[0012] In some embodiments of the first aspect of the present application, the nanofiber includes at least one of polyvinylidene fluoride, polyimide, polyamide, polyacrylonitrile, polyethylene glycol, polyphenylene ether, polypropylene carbonate, polymethyl methacrylate, polyethylene terephthalate, polyethylene oxide, polyvinylidene fluoride-hexafluoropropylene or polyvinylidene fluoride-chlorotrifluoroethylene.
[0013] In some embodiments of the first aspect of the present application, the isolation layer also includes a polymer layer, which is disposed on the porous layer; the thickness of the polymer layer is 0.05 μm to 4 μm, and the coverage area ratio of the polymer layer on the porous layer is 10% to 70%.
[0014] In some embodiments of the first aspect of the present application, the polymer layer includes polymer aggregates, and the polymer aggregates have at least one of the following characteristics:
[0015] (a) The maximum coverage area of a single polymer aggregate in the polymer layer is 1×10 -5 mm 2 ~1mm 2 , preferably 0.001m 2 ~0.05mm 2 ;
[0016] (b) the depth of the polymer aggregates in the polymer layer embedded in the porous layer accounts for 0.01% to 80% of the thickness of the porous layer;
[0017] (c) The depth of the polymer aggregates in the polymer layer embedded in the porous layer accounts for 10% to 80% of the thickness of the polymer aggregates.
[0018] In some embodiments of the first aspect of the present application, the polymer layer has a regular pattern.
[0019] In some embodiments of the first aspect of the present application, the isolation layer further includes an inorganic compound layer, the inorganic compound layer includes inorganic particles, and the inorganic compound layer is disposed on the porous layer.
[0020] In some embodiments of the first aspect of the present application, the inorganic compound layer has at least one of the following characteristics:
[0021] (a) a portion of the inorganic particles in the inorganic compound layer are embedded in the porous layer;
[0022] (b) the depth to which the inorganic particles of the inorganic compound layer are embedded in the porous layer accounts for 0.01% to 80% of the thickness of the porous layer;
[0023] (c) The electronic resistivity of the inorganic compound layer is greater than 10 7 Ω·m;
[0024] (d) The ionic conductivity of the inorganic compound layer is 10 -8 S / cm~10 -2 S / cm;
[0025] (e) the thickness of the inorganic compound layer is 0.1 μm to 20 μm;
[0026] (f) The inorganic compound layer has a porosity of 10% to 40% and a pore size of 0.001 μm to 8 μm.
[0027] In some embodiments of the first aspect of the present application, the inorganic compound layer is provided by spraying or deposition.
[0028] In some embodiments of the first aspect of the present application, the inorganic compound layer and the porous layer are bonded by heat pressing or bonding.
[0029] In some embodiments of the first aspect of the present application, the average pore size of the porous layer varies in the thickness direction.
[0030] In some embodiments of the first aspect of the present application, the average pore size of the porous layer closer to the electrode pad area is smaller than the average pore size of the porous layer farther away from the electrode pad area.
[0031] In some embodiments of the first aspect of the present application, the porous layer is prepared by electrospinning, air spinning or centrifugal spinning.
[0032] A second aspect of the present application provides an electronic device, which includes the electrochemical device provided by the first aspect of the present application.
[0033] The electrochemical device provided by the solution of the present application provides a porous layer on the surface of the electrode plate (such as the positive electrode plate and / or the negative electrode plate) to replace the ordinary isolation membrane, thereby isolating electrons and conducting ions; further, compared with the ordinary isolation membrane, the porous layer has a smaller thickness and a stronger liquid retention capacity, thereby enabling the electrochemical device to have a higher energy density. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the embodiments of the present application and the technical solutions of the prior art, the following briefly introduces the drawings required for use in the embodiments and the prior art. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0035] Figure 1 This is a SEM photo of the surface of the isolation layer of the electrochemical device of Example 1 (500 times);
[0036] Figure 2 This is a SEM photo of the surface of the isolation layer of the electrochemical device of Example 1 (2000 times);
[0037] Figure 3 This is a SEM photograph of a cross section of the isolation layer of the electrochemical device of Example 1; the arrows point to polymer aggregate particles embedded in the porous layer. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical scheme, and advantages of the present application more clearly understood, the present application is further described in detail with reference to the accompanying drawings and embodiments. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.
[0039] The electrochemical device of the present application may be any electrochemical device using an electrode plate and an isolation layer of the present application that are well known to those skilled in the art, such as a lithium-ion battery, a sodium-ion battery, a magnesium-ion battery, a supercapacitor, etc., and the following description is made using a lithium-ion battery as an example. Those skilled in the art should understand that the following description is only for illustrative purposes and does not limit the scope of protection of the present application.
[0040] The present application provides an electrochemical device, including an electrode plate and an isolation layer formed on the surface of the electrode plate, wherein the isolation layer includes a porous layer formed on the surface of the electrode plate; the porous layer includes nanofibers, and the electrolyte injection property of the isolation layer is less than 15 seconds.
[0041] In the process of assembling lithium-ion batteries, usually, the electrolyte is injected into a sealed cavity (such as a packaging shell) through a quantitative pump, the lithium-ion battery is placed in the injection chamber, and then the injection chamber is evacuated with a vacuum pump, and a vacuum environment is formed inside the lithium-ion battery. Then the injection nozzle is inserted into the injection port of the lithium-ion battery, the electrolyte injection valve is opened, and the electrolyte chamber is pressurized with nitrogen at the same time. The pressure is maintained for a certain period of time, and the injection chamber is vented to normal pressure, and finally left to stand for a long time, so that the electrolyte can fully infiltrate the positive electrode sheet, the negative electrode sheet and the isolation layer. When the injection is completed, the lithium-ion battery is sealed. Generally speaking, during the injection process, the electrolyte first penetrates into the isolation layer, and then gradually penetrates into the positive and negative electrode materials. Therefore, injection property is an important indicator of lithium-ion batteries. Traditional isolation membranes mainly use polyethylene microporous membranes or polypropylene microporous membranes or a combination of the two, and their injection properties have certain limitations. The present application adopts the method of setting an isolation layer containing nanofibers on the surface of the electrode plate, so that the electrolyte injection performance of the isolation layer reaches less than 15 seconds, which can significantly improve the injection performance of the lithium-ion battery.
[0042] In addition, the nanofiber porous layer has good adhesion to the electrode plate, which can effectively prevent the isolation membrane from being washed away by the electrolyte and folded when a conventional isolation membrane is used in the lithium-ion battery during the falling process, thereby improving the safety of the lithium-ion battery.
[0043] The electrode plates mentioned in the present application may be positive electrode plates and / or negative electrode plates, and the isolation layer may be arranged on the positive electrode plates and / or the negative electrode plates to isolate the positive electrode plates from the negative electrode plates; in addition, the isolation layer may be arranged on one surface or both surfaces of the positive electrode plates or the negative electrode plates, and the present application does not limit this.
[0044] In some embodiments of the present application, when the thickness of the isolation layer is converted to 20 μm, the air permeability is 5 s / 100 cm 3 ~400s / 100cm 3 The inventors of the present application have found that when the air permeability of the isolation layer is within the above range, the liquid injection property of the isolation layer is significantly improved.
[0045] In some embodiments of the present application, the porosity of the isolation layer is 30% to 95%. When the porosity of the isolation layer is within the above range, the lithium-ion battery of the present application has good liquid injection and high ion conductivity. In other embodiments of the present application, the average pore size of the porous layer is 20nm to 10μm. When the pore size is less than 20nm, the liquid injection decreases and the ion conductivity decreases; when the pore size is greater than 10μm, the pore size is too large, and the electrode active material in the electrode plate may pass through the isolation layer, causing a short circuit and self-discharge. When the thickness of the isolation layer is too small, the isolation layer cannot play a good role in isolating the electrons between the positive and negative electrodes, and the self-discharge increases. When the thickness of the isolation layer is too large, the energy density of the lithium-ion battery will be significantly reduced; in other embodiments of the present application, the thickness of the isolation layer is 1μm to 20μm; preferably 2μm to 18μm, more preferably 5μm to 15μm, and most preferably 8μm to 12μm.
[0046] In some embodiments of the present application, the diameter of the nanofiber is 0.1nm to 2μm. If the diameter of the nanofiber is too small, the strength of the fiber itself is too low, which may easily lead to the disconnection of the nanofiber during the preparation or use of the lithium-ion battery, and the isolation layer is pierced by the electrode active material particles, resulting in self-discharge; if the diameter of the nanofiber is too large, the volume occupied by the nanofiber in the isolation layer is too large, and when the isolation layer contains the same weight of nanofibers, the pore size of the isolation layer may be too large. When the isolation layer maintains the same porosity, the nanofiber content decreases, resulting in a decrease in the strength of the isolation layer and an excessively large pore size.
[0047] In some embodiments of the present application, the nanofiber includes at least one of a polymer such as polyvinylidene fluoride, polyimide, polyamide, polyacrylonitrile, polyethylene glycol, polyphenylene oxide, polypropylene carbonate, polymethyl methacrylate, polyethylene terephthalate, polyethylene oxide, polyvinylidene fluoride-hexafluoropropylene or polyvinylidene fluoride-chlorotrifluoroethylene. Preferably, the nanofiber includes a lithium ion conductor material, such as polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyphenylene oxide, polypropylene carbonate, polyethylene oxide, etc. and their derivatives. These polymers can be used alone or in combination of two or more.
[0048] In some embodiments of the present application, the isolation layer also includes a polymer layer, the thickness of the polymer layer is 0.05 μm to 4 μm, and the polymer layer is covered on the nanofiber porous layer, and the coverage area ratio of the nanofiber porous layer is 10% to 70%, preferably 20% to 40%. The polymer layer can improve the mechanical strength of the isolation layer and reduce the K value (the voltage drop of the battery per unit time, mV / d; an indicator of the self-discharge rate of the battery). In addition, when there are larger pores in the nanofiber porous layer, the polymer layer can cover these pores with larger pore sizes to reduce self-discharge. If the coverage area is too small, the effect on reducing the K value is not obvious, and the effect on increasing the mechanical strength of the isolation layer is not obvious. If the coverage area is too large, the ion conduction of the isolation layer is affected and the rate performance is reduced. In addition, the polymer layer can also improve the bonding performance between the isolation layer and the electrode pole piece in contact with its surface. During the winding process of the lithium-ion battery, the sliding between the isolation layer and the electrode pole piece is prevented.
[0049] The polymer layer includes polymer aggregates, wherein the single polymer aggregate refers to an aggregate formed by agglomeration of one or more polymer secondary particles; it can be understood that the polymer aggregate can be an aggregate containing multiple polymer secondary particles or a single polymer secondary particle. The inventor of the present application has found through in-depth research that in order to achieve a better effect, the maximum coverage area of a single polymer aggregate is 1×10 -5 mm 2 ~1mm 2 , preferably 0.001m 2 ~0.05mm 2 If the volume of a single polymer aggregate is too small, the bonding effect of the electrode plate in contact with it is limited, and the ability to improve the pore size of the porous layer is insufficient, that is, it cannot effectively cover the larger pores in the nanofiber porous layer, and therefore cannot effectively prevent self-discharge. If the volume of a single polymer aggregate is too large, it will affect the local ion transport, resulting in inconsistent charging and discharging of the lithium-ion battery as a whole, causing a decrease in the cycle capacity and cycle capacity retention rate at high rates.
[0050] In a preferred embodiment of the present application, the polymer aggregates are embedded in the porous layer, such as Figure 3As shown. The embedding of polymer aggregates in the porous layer can reduce the number of larger pores, that is, reduce the pore diameter, and on the other hand, can make the polymer aggregates relatively fixed in the porous layer to avoid slippage. In addition, since the polymer aggregates are embedded in the porous layer, the relative slippage between the nanofibers in the porous layer will also be reduced. The inventors of the present application found that the depth of the polymer aggregates embedded in the porous layer is preferably 0.5 to 5 μm, and more preferably 1 to 2 μm. If the embedding depth is too small, it is difficult to effectively fill the pores in the porous layer, the effect of reducing self-discharge is limited, and it is not conducive to enhancing the riveting effect and bonding effect of the polymer aggregates and the porous layer, and the relative movement between the nanofibers in the porous layer and the relative movement between the polymer aggregates and the nanofibers cannot be well prevented. If the embedding depth is too deep, it will affect the local ion transport, resulting in inconsistent charging and discharging of the lithium-ion battery as a whole, and reducing the cycle capacity and cycle capacity retention rate at a large rate.
[0051] It should be noted that when a polymer layer is coated on a conventional isolation membrane, the thickness of the surface of the isolation membrane will generally increase by 5 to 10 μm, and the thickness increase is very uneven. In some locations where the polymer aggregates are large, the thickness increases more. After the lithium-ion battery is injected and hot-pressed, the thickness increase will be reduced to 0.5 to 1 μm, but the heterogeneity still exists. However, when the polymer layer is coated on the porous layer of the present application, the polymer aggregates are only coated on the surface of the porous layer, and the thickness increases by only less than 1 μm. After the lithium-ion battery is injected and hot-pressed, the thickness is thinner. Without being limited to any theory, the inventor believes that because the pores in the porous layer are relatively large, the polymer aggregates will be embedded in the pores, which has little effect on the thickness of the isolation layer.
[0052] In some preferred embodiments of the present application, the depth of the polymer aggregates embedded in the porous layer accounts for 0.01% to 80% of the thickness of the porous layer. If the embedding depth is too small, the riveting effect and bonding effect of the polymer aggregates on the porous layer are insufficient. If the embedding depth is too large, it may lead to insufficient bonding between the isolation layer and the electrode plate.
[0053] In some preferred embodiments of the present application, the portion of the polymer aggregate embedded in the porous layer accounts for 10% to 80% of the polymer aggregate thickness, preferably 40% to 60%. If the embedding depth ratio is too small, it is not conducive to enhancing the riveting effect and bonding effect between the polymer aggregate and the porous layer, and the bonding force between the electrode plate and the isolation layer is limited; if the embedding depth ratio is too large, the area of the polymer aggregate exposed to the outside will be reduced, which is also not conducive to the interface bonding between the electrode plate and the isolation layer. The scanning electron microscope (SEM) photo of the embedding effect is shown in FIG. Figure 3 shown.
[0054] In some preferred embodiments of the present application, the polymer layer may have a regular pattern. The method for forming the pattern is not particularly limited, and can be carried out by methods known to those skilled in the art, for example, using a gravure roller engraved with a special pattern to transfer-coat the polymer layer, or using a mask to cover part of the position, exposing the position where the polymer layer needs to be prepared to coat the polymer layer, and a polymer layer with a regular pattern can be prepared. The pattern of the polymer layer is not particularly limited, and can be dot-shaped, stripe-shaped, block-shaped, linear, etc. The polymer layer with a regular pattern can make the interfacial adhesion distribution more uniform, and the pore filling is more uniform, thereby reducing local residual macropores and reducing the risk of local short circuits caused by poor local mechanical strength.
[0055] The polymer forming the polymer layer is not particularly limited and can be selected from any polymer known in the art, such as polyvinylidene fluoride, polyimide, polyamide, polyacrylonitrile, polyethylene glycol, polyphenylene ether, polypropylene carbonate, polymethyl methacrylate, polyethylene terephthalate, polyethylene oxide, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-chlorotrifluoroethylene copolymer and one or more of their derivatives. These polymers can be used alone or in combination of two or more.
[0056] In some preferred embodiments of the present application, the isolation layer may further include an inorganic compound layer disposed on the porous layer, wherein the inorganic compound layer includes inorganic particles and an adhesive. The inorganic compound layer can further improve the mechanical strength of the isolation layer and ensure the insulation performance, and reduce the electronic conductivity of the isolation layer. Preferably, part of the inorganic particles in the inorganic compound layer are embedded in the porous layer, and the mechanical strength of the isolation layer can be further improved through the riveting effect of the inorganic particles on the fiber porous layer. Preferably, the depth of the inorganic particles embedded in the porous layer accounts for 0.01% to 80% of the thickness of the porous layer. If the embedding depth of the inorganic particles is too small, the riveting effect is not obvious. If the embedding depth is too large, it may penetrate the entire porous layer, reducing the protective effect of the inorganic compound layer. Preferably, the electronic resistivity of the inorganic compound layer is greater than 10 7 Ω·m, more preferably, the electronic resistivity is greater than 10 10 Ω·m, thereby reducing the electronic conductivity of the isolation layer. Preferably, the inorganic compound layer has good ionic conductivity, for example, its ionic conductivity is 10 -8 S / cm~10 -2 S / cm. The thickness of the inorganic compound layer is not particularly limited as long as the purpose of the present application is achieved. For example, the thickness of the inorganic compound layer is 0.1 μm to 20 μm. The porosity of the inorganic compound layer is not particularly limited as long as the purpose of the present application is achieved. For example, the porosity of the inorganic compound layer is 10% to 40% and the pore size is 0.001 μm to 8 μm.
[0057] In a preferred embodiment of the present application, the inorganic particles are selected from inorganic compounds such as HfO2, SrTiO3, SnO2, CeO2, MgO, NiO, CaO, BaO, ZnO, ZrO2, Y2O3, Al2O3, TiO2, SiO2, boehmite, magnesium hydroxide, aluminum hydroxide, or materials having lithium ion conductivity, such as lithium phosphate (Li3PO4), lithium titanium phosphate (Li x Ti y (PO4)3, wherein 0<x<2 and 0<y<3), lithium aluminum titanium phosphate (Li x Al y Ti z (PO4)3, where 0<x<2, 0<y<1, and 0<z<3), where 0≤x≤1 and 0≤y≤1 Li 1+x+y (Al, Ga) x (Ti, Ge) 2-x Si y P 3-y O 12 , lithium lanthanum titanate (Li x La y TiO3, wherein 0<x<2 and 0<y<3), lithium germanium thiophosphate (Li x Ge y P z S w , where 0<x<4, 0<y<1, 0<z<1, and 0<w<5), lithium nitride (Li x N y , where 0<x<4, 0<y<2), SiS2 glass (Li x Si y S z , where 0≤x<3, 0<y<2, and 0<z<4), P2S5 glass (Li x P y S z , where 0≤x<3, 0<y<3, and 0<z<7), Li2O, LiF, LiOH, Li2CO3, LiAlO2, Li2O-Al2O3-SiO2-P2O5-TiO2-GeO2 ceramics, and garnet ceramics (Li 3+x La3M2O 12 , wherein 0≤x≤5, and M is Te, Nb or Zr), these inorganic particles can be used alone or in combination of two or more.
[0058] The method for preparing the inorganic compound layer is not particularly limited and can be carried out by methods known in the art, such as spraying or deposition, preferably electrospraying.
[0059] There is no particular limitation on the bonding method between the inorganic compound layer and the porous layer, and it can be carried out by methods known in the art. For example, the inorganic compound layer and the porous layer can be bonded by heat pressing or bonding.
[0060] In a preferred embodiment of the present application, the average pore size of the porous layer varies in the thickness direction, and the pore size refers to the pore size of the pores formed by the nanofibers in the porous layer. By changing the average pore size in the thickness direction, the ion conductivity of the porous layer can be optimized, while preventing short circuit or self-discharge due to excessive pore size. Preferably, the average pore size of the porous layer closer to the electrode plate area is smaller than the average pore size farther away from the electrode plate area.
[0061] The type of lithium-ion battery according to the present application is not limited, and can be any type of lithium-ion battery, such as button-type, cylindrical, square, soft-pack, hard-shell lithium-ion battery, etc. The lithium-ion battery according to the present application includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separation layer according to the present application.
[0062] In one embodiment of the present application, a separation layer may be formed on one surface of the positive electrode sheet and on one surface of the negative electrode sheet, and then stacked in the manner of negative electrode sheet + separation layer, positive electrode sheet + separation layer to form a lithium-ion battery stack. In another embodiment of the present application, a separation layer may be formed on both surfaces of the positive electrode sheet, and then stacked in the manner of negative electrode sheet, separation layer + positive electrode sheet + separation layer to form a lithium-ion battery stack, wherein there is no separation layer on the surface of the negative electrode sheet. In another embodiment of the present application, a separation layer may be formed on both surfaces of the negative electrode sheet, and then stacked in the manner of separation layer + negative electrode sheet + separation layer, positive electrode sheet to form a lithium-ion battery stack. The stack formed in the above embodiment may continue to be stacked in the above order, or may be directly wound to form a multi-layer lithium-ion battery stack. The present application does not limit the stacking method, and those skilled in the art may choose according to actual conditions.
[0063] In the embodiments of the present application, the positive electrode sheet is not particularly limited, as long as the purpose of the present application can be achieved. For example, the positive electrode sheet generally includes a positive current collector and a positive active material layer. Among them, the positive current collector is not particularly limited, and can be any positive current collector known in the art, such as copper foil, aluminum foil, aluminum alloy foil, and composite current collector. The positive active material layer includes a positive active material, and the positive active material is not particularly limited, and can be any positive active material of the prior art. The positive active material may include lithium nickel cobalt manganese oxide (811, 622, 523, 111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium iron manganese phosphate, or at least one of lithium titanate.
[0064] Optionally, the positive electrode sheet may further include a conductive layer, the conductive layer being located between the positive electrode current collector and the positive electrode active material layer. The composition of the conductive layer is not particularly limited, and may be a conductive layer commonly used in the art. For example, the conductive layer may include a conductive agent and a binder.
[0065] In the embodiments of the present application, the negative electrode plate is not particularly limited as long as the purpose of the present application can be achieved. For example, the negative electrode plate generally comprises a negative electrode current collector and a negative electrode active material layer. Among them, the negative electrode current collector is not particularly limited, and any negative electrode current collector known in the art can be used, such as copper foil, aluminum foil, aluminum alloy foil, and composite current collector. The negative electrode active material layer includes a negative electrode active material, and the negative electrode active material is not particularly limited, and any negative electrode active material known in the art can be used. For example, it can include at least one of artificial graphite, natural graphite, mesophase carbon microspheres, soft carbon, hard carbon, silicon, silicon carbon, lithium titanate, etc.
[0066] Optionally, the negative electrode plate may further include a conductive layer, which is located between the negative electrode current collector and the negative electrode active material layer. The composition of the conductive layer is not particularly limited, and may be a conductive layer commonly used in the art. For example, the conductive layer includes a conductive agent and a binder.
[0067] The above-mentioned conductive agent is not particularly limited, and any conductive agent known in the art can be used, as long as the purpose of the present application can be achieved. For example, the conductive agent can be selected from at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fiber, Ketjen black, and graphene. For example, the conductive agent can be selected from conductive carbon black (Super P). The above-mentioned adhesive is not particularly limited, and any adhesive known in the art can be used, as long as the purpose of the present application can be achieved. For example, the adhesive can be selected from at least one of polyvinylidene fluoride, polyacrylic acid, polyacrylate, styrene-butadiene rubber (SBR), polyvinyl alcohol (PVA), polytetrafluoroethylene (PTFE), and sodium carboxymethyl cellulose (Na-CMC). For example, the adhesive can be selected from styrene-butadiene rubber (SBR).
[0068] The electrolyte of the lithium-ion battery is not particularly limited, and any electrolyte known in the art can be used, for example, any one of a gel state, a solid state and a liquid state. For example, a liquid electrolyte may include a lithium salt and a non-aqueous solvent.
[0069] The lithium salt is not particularly limited, and any lithium salt known in the art can be used as long as the purpose of the present application can be achieved. For example, the lithium salt can be selected from at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3 and LiPO2F2. For example, the lithium salt can be LiPF6.
[0070] The non-aqueous solvent is not particularly limited as long as the purpose of the present application can be achieved. For example, the non-aqueous solvent can be selected from at least one of carbonate compounds, carboxylate compounds, ether compounds, nitrile compounds, and other organic solvents.
[0071] For example, the carbonate compound can be selected from at least one of diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methylpropyl carbonate (MPC), ethylpropyl carbonate (EPC), ethyl methyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC), fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, and trifluoromethylethylene carbonate.
[0072] There is no limitation on the preparation method of the electrochemical device of the present application. For example, nanofibers may be deposited on one or both surfaces of the positive electrode sheet or the negative electrode sheet to form a porous layer containing nanofibers.
[0073] In a preferred embodiment, the method for preparing the electrochemical device of the present application further comprises depositing a porous layer containing nanofibers on the surface of the electrode plate and then depositing a polymer layer.
[0074] The method of depositing the nanofiber porous layer and the polymer layer is not particularly limited, and can be carried out by a deposition method known in the art. For example, the porous layer can be prepared by electrospinning, air spinning or centrifugal spinning, and the polymer layer can be prepared by electrospraying. For example, nanofibers can be deposited first to form a porous layer, and then polymer aggregates can be deposited to form a polymer layer on the surface of the porous layer.
[0075] The porous layer can be implemented with any spinning equipment known in the art without any particular limitation, as long as the purpose of the present application can be achieved. For example, the electrospinning equipment can be the Yongkang Leye Elite series, etc.; the air spinning equipment can be the air-jet spinning machine of Nanjing Jienas New Materials, etc.; the centrifugal spinning equipment can be the centrifugal spinning machine of Sichuan Zhiyan Technology, etc. The electrospraying method can be implemented with any equipment known in the art without any particular limitation, as long as the purpose of the present application can be achieved. For example, the electrostatic spraying equipment of Sames, France can be used.
[0076] In a preferred embodiment, the preparation method of the present application further comprises depositing a porous layer containing nanofibers on the surface of the electrode plate and then depositing an inorganic compound layer.
[0077] The deposition method of the inorganic compound layer is not particularly limited, and can be carried out, for example, by electrodeposition. The nanofiber spinning of the porous layer and the deposition of the inorganic compound layer can be carried out simultaneously, or the nanofiber porous layer can be first spun and then the inorganic compound layer can be deposited, or the nanofiber porous layer can be first deposited and then the inorganic compound layer can be deposited, and the process can be repeated multiple times to alternately form multiple nanofiber porous matrices and inorganic compound layers.
[0078] The present application also provides an electronic device, which includes the electrochemical device according to the present application.
[0079] The terms used in this application are generally terms commonly used by those skilled in the art. If there is any inconsistency with commonly used terms, the terms in this application shall prevail.
[0080] Specifically, in this application, the following terms have the following meanings:
[0081] Porosity: The percentage of the volume of pores in the isolation layer or inorganic compound layer to the total volume of the isolation layer or inorganic compound layer, which can be tested using the mercury injection method.
[0082] Polymer aggregate thickness: refers to the thickness of a single polymer aggregate in the direction perpendicular to the plane of the porous layer.
[0083] Test method:
[0084] Lithium-ion battery self-discharge rate K value:
[0085] The lithium-ion battery was discharged at a current of 0.5C to 3.0V, and then left to stand for 5 minutes. Then, the lithium-ion battery was charged at a constant current of 0.5C to 3.85V, and then charged at a constant voltage of 3.85V to a current of 0.05C, and left to stand for two days in an environment of 25℃±3℃, and the voltage OCV1 at this time was tested and recorded. Then, the lithium-ion battery was left to stand for two days in an environment of 25℃±3℃, and the voltage OCV2 at this time was tested and recorded, and the K value was obtained by the following formula: K (mV / h) = (OCV2-OCV1) / 48h*1000.
[0086] Capacity retention rate:
[0087] The lithium-ion battery is charged to 4.4V at a constant current of 0.5C, then charged to a current of 0.05C at a constant voltage of 4.4V, left to stand at 25℃±3℃ for 10min, then discharged to 3.0V at a current of 0.5C, and the first discharge capacity is recorded as Q1. This cycle is repeated 50 times, and the discharge capacity at this time is recorded as Q 50 The capacity retention rate η after 50 cycles is obtained by the following formula: η=Q 50 / Q1*100%.
[0088] Example
[0089] Preparation Example 1: Preparation of negative electrode sheet
[0090] Mix the negative electrode active materials artificial graphite, conductive carbon black, and styrene-butadiene rubber in a weight ratio of 96:1.5:2.5, add deionized water as a solvent, prepare a slurry with a solid content of 0.7, and stir evenly. The slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 8μm, and dried at 110°C to obtain a negative electrode sheet with a single-sided coating of a negative electrode active material layer with a thickness of 130μm. Repeat the above steps on the other surface of the negative electrode current collector to obtain a negative electrode sheet with a double-sided coating of a 130μm thick negative electrode active material layer. Then, cut the negative electrode sheet into a specification of 41mm×61mm for standby use.
[0091] Preparation Example 2: Preparation of positive electrode sheet
[0092] The positive electrode active material lithium cobalt oxide, conductive carbon black, and polyvinylidene fluoride are mixed in a weight ratio of 97.5:1.0:1.5, and N-methylpyrrolidone (NMP) is added as a solvent to prepare a slurry with a solid content of 0.75, and stirred evenly. The slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 10μm, and dried at 90°C to form a positive electrode active material layer with a thickness of 110μm on one side of the positive electrode current collector. On the other surface of the positive electrode current collector aluminum foil, the above steps are repeated to obtain a positive electrode sheet coated with a 100μm positive electrode active material layer on both sides. After coating, the positive electrode sheet is cut into a specification of 38mm×58mm for standby use.
[0093] Preparation Example 3: Preparation of electrolyte
[0094] In a dry argon atmosphere, ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are first mixed as a solvent in a mass ratio of EC:EMC:DEC=30:50:20, and then lithium salt lithium hexafluorophosphate (LiPF6) is added to the solvent to dissolve and mix evenly to obtain an electrolyte with a lithium salt concentration of 1.15 mol / L.
[0095] The following examples illustrate the preparation of an integrated isolation layer of a nanofiber porous layer + a polymer layer according to the present application. These embodiments are described by taking the positive electrode plate as an example, and an integrated isolation layer is deposited on both surfaces of the positive electrode plate. It should be understood that the integrated isolation layer can also be deposited on both surfaces of the negative electrode plate, or an integrated isolation layer can be deposited on one surface of the positive electrode plate and one surface of the negative electrode plate, respectively. These embodiments can also achieve the purpose of the present application; in addition, the integrated isolation layer can also be an integrated isolation layer of a nanofiber porous layer + an inorganic compound layer. Those skilled in the art should understand that these embodiments are also within the scope of protection of the present application.
[0096] Example 1
[0097] A porous layer (containing PVDF) with a thickness of 12 μm and an average pore size of 150 nm and a nanofiber diameter of 600 nm was prepared on one surface of the positive electrode sheet obtained in Preparation Example 2 by a mixed method of electrospinning and air spinning;
[0098] The polyvinylidene fluoride and polyacrylate are mixed in a mass ratio of 96:4 and dissolved in deionized water to form a polymer layer slurry, wherein the Dv50 of the polyvinylidene fluoride is 600 nm. The polymer layer slurry is then uniformly coated on the surface of the porous layer by a micro-concave coating method, and then dried to obtain a polymer layer;
[0099] The total coverage of the polymer layer is 10%, and the maximum coverage of a single polymer aggregate is 0.1 mm 2 The depth of polymer aggregates embedded in the porous layer is 1 μm, the depth of polymer aggregates embedded in the porous layer accounts for 25% of the thickness of polymer aggregates, and the depth of polymer aggregates embedded in the porous layer accounts for 8.3% of the thickness of the porous layer. The porosity of the isolation layer is 80%, the thickness is 15 μm, and the air permeability when converted to 20 μm is 112 s / 100 cm 3 Then repeat the above steps on the other surface of the positive electrode sheet and dry it at 90°C to remove the solvent in the polymer layer to obtain a double-sided coated positive electrode sheet. Figure 1 , Figure 2 shown.
[0100] Example 2
[0101] In addition to the total coverage ratio of the polymer layer of 30%, the air permeability of the isolation layer when converted to 20μm is 123s / 100cm 3 Other than that, the rest is the same as Example 1.
[0102] Example 3
[0103] In addition to the total coverage ratio of the polymer layer of 70%, the air permeability of the isolation layer when converted to 20μm is 137s / 100cm 3 Other than that, the rest is the same as Example 1.
[0104] Example 4
[0105] In addition to the maximum coverage area of a single polymer aggregate of 1×10 -5 mm 2 Except that the average pore diameter of the porous layer is 80 nm, the rest is the same as Example 2.
[0106] Example 5
[0107] In addition, the maximum coverage area of a single polymer agglomerate is 0.01 mm 2 Except that the average pore diameter of the porous layer is 100 nm, the rest is the same as Example 2.
[0108] Example 6
[0109] In addition to the maximum coverage area of a single polymer agglomerate of 1 mm 2 Except that the average pore diameter of the porous layer is 400 nm, the rest is the same as Example 2.
[0110] Example 7
[0111] The same as in Example 5 except that the depth of the polymer aggregates embedded in the nanofiber porous layer is 0.5 μm and the ratio of the depth of the polymer aggregates embedded in the porous layer to the thickness of the polymer aggregates is 14%.
[0112] Example 8
[0113] The same as in Example 5 except that the depth of the polymer aggregates embedded in the nanofiber porous layer is 0.8 μm and the ratio of the depth of the polymer aggregates embedded in the porous layer to the thickness of the polymer aggregates is 21%.
[0114] Example 9
[0115] The same as in Example 5 except that the depth of the polymer aggregates embedded in the nanofiber porous layer is 1.5 μm and the depth of the polymer aggregates embedded in the porous layer accounts for 33% of the thickness of the polymer aggregates.
[0116] Example 10
[0117] The same as in Example 5 except that the depth of the polymer aggregates embedded in the nanofiber porous layer is 3.0 μm and the depth of the polymer aggregates embedded in the porous layer accounts for 50% of the thickness of the polymer aggregates.
[0118] Embodiment 11
[0119] The same as in Example 5 except that the depth of the polymer aggregates embedded in the nanofiber porous layer is 5.0 μm and the ratio of the depth of the polymer aggregates embedded in the porous layer to the thickness of the polymer aggregates is 62.5%.
[0120] Example 12
[0121] The same as in Example 5 except that the depth of the polymer aggregates embedded in the nanofiber porous layer is 8.0 μm and the depth of the polymer aggregates embedded in the porous layer accounts for 72.5% of the thickness of the polymer aggregates.
[0122] Embodiment 13
[0123] The process is the same as that of Example 5 except that the polymer layer has a striped pattern.
[0124] Embodiment 14
[0125] The process is the same as that of Example 5 except that the polymer layer has a dot pattern.
[0126] Embodiment 15
[0127] The process is the same as that of Example 5 except that the polymer layer has a block pattern.
[0128] Example 16
[0129] The process is the same as that of Example 5 except that the average pore size of the porous layer is adjusted to 500 nm.
[0130] Embodiment 17
[0131] The same as Example 5 except that the thickness of the porous layer is adjusted to 4 μm, the depth of polymer aggregates embedded in the porous layer is 1 μm, the thickness of the isolation layer is 5 μm, and the depth of polymer aggregates embedded in the porous layer accounts for 50% of the thickness of polymer aggregates.
[0132] Embodiment 18
[0133] Except that the porosity of the isolation layer is adjusted to 95%, the rest is the same as Example 5.
[0134] Embodiment 19
[0135] Except that the nanofiber material is replaced by polyethylene oxide (PEO), the rest is the same as Example 5.
[0136] Embodiment 20
[0137] On one surface of the positive electrode plate obtained in Preparation Example 2, a porous layer (composed of PVDF) with a thickness of 12 μm was prepared by a mixed method of electrospinning and air spinning, the diameter of the nanofibers was 600 nm, the average pore size of the porous layer closer to the positive electrode plate was 100 nm, and the average pore size of the porous layer farther away from the positive electrode plate was 500 nm, and the average pore size of the porous layer gradually increased from the area closer to the positive electrode plate to the area farther away from the positive electrode plate.
[0138] Polyvinylidene fluoride and polyacrylate are mixed in a mass ratio of 96:4 and dissolved in deionized water to form a polymer layer slurry, wherein the Dv50 of the polyvinylidene fluoride is 600 nm. The polymer layer slurry is then uniformly coated on the surface of the porous layer by a micro-concave coating method, and dried to obtain a polymer layer.
[0139] The total coverage of the polymer layer is 30%, and the maximum coverage of a single polymer aggregate is 0.01 mm 2 , the depth of polymer agglomerates embedded in the porous layer is 1.5 μm, the depth of polymer agglomerates embedded in the porous layer accounts for 50% of the thickness of polymer agglomerates, the depth of polymer agglomerates embedded in the porous layer accounts for 8.3% of the thickness of the porous layer, the porosity of the isolation layer is 80%, and the thickness is 15 μm. Then repeat the above steps on the other surface of the positive electrode sheet, and dry at 90°C to remove the solvent in the polymer layer to obtain a double-sided coated positive electrode sheet.
[0140] Embodiment 21
[0141] Preparation of negative electrode
[0142] Conductive carbon black and styrene-butadiene rubber were mixed at a weight ratio of 95:5, and deionized water was added as a solvent to prepare a slurry with a solid content of 0.8, and the mixture was stirred evenly. The slurry was evenly coated on the two surfaces of a negative electrode current collector copper foil with a thickness of 8 μm, and dried at 110°C to obtain a negative electrode conductive layer with a single-side thickness of 2 μm.
[0143] The negative electrode active material graphite, conductive carbon black, and styrene-butadiene rubber are mixed in a weight ratio of 96:1.5:2.5, and deionized water is added as a solvent to prepare a slurry with a solid content of 0.7, and stirred evenly. The slurry is evenly coated on the above conductive layer and dried at 110°C to obtain a negative electrode sheet with a thickness of 130μm and a single-sided coating of negative electrode active material. Repeat the above steps on the other surface of the negative electrode sheet to obtain a negative electrode sheet with a double-sided coating of negative electrode active material. Then, the sheet is cut into a specification of 41mm×61mm for standby use.
[0144] Preparation of positive electrode
[0145] Conductive carbon black and styrene-butadiene rubber were mixed in a weight ratio of 97:3, deionized water was added as a solvent, and a slurry with a solid content of 0.85 was prepared and stirred evenly. The slurry was evenly coated on the two surfaces of the positive electrode current collector aluminum foil with a thickness of 10 μm, and dried at 110°C to obtain a positive electrode conductive layer with a single-side thickness of 2 μm.
[0146] The positive electrode active material lithium cobalt oxide, conductive carbon black, and polyvinylidene fluoride are mixed in a weight ratio of 97.5:1.0:1.5, and N-methylpyrrolidone (NMP) is added as a solvent to prepare a slurry with a solid content of 0.75, and stirred evenly. The slurry is evenly coated on the above-mentioned positive electrode conductive layer, and dried at 90°C to obtain a positive electrode sheet coated with a 100μm positive electrode active material layer on both sides. After coating, the sheet is cut into a specification of 38mm×58mm for standby use.
[0147] Then, the procedure of Example 5 was repeated.
[0148] Embodiment 22
[0149] Using the positive electrode sheet with a positive electrode conductive layer obtained in Example 21, an isolation layer was prepared according to the following steps.
[0150] On one surface of the positive electrode sheet, a porous layer (composed of PVDF) with a thickness of 12 μm was prepared by a mixed method of electrospinning and air spinning, with an average pore size of 100 nm and a nanofiber diameter of 600 nm.
[0151] Boehmite and sodium hydroxymethyl cellulose were dispersed in a dimethylformamide / acetone (7:3) solvent and stirred evenly until the slurry viscosity was stable to obtain a suspension with a mass fraction of 40% as a slurry. The suspension was sprayed on the surface of the positive electrode sheet with a porous layer by an electrospraying method to form an inorganic compound layer with a thickness of 3 μm and a conductivity of 10 8 Ω·m, ionic conductivity is 10 -5 S / cm, the average pore size is 0.5 μm, the depth of the inorganic particles embedded in the porous layer accounts for 8.3% of the thickness of the porous layer, and the thickness of the isolation layer is 15 μm.
[0152] Embodiment 23
[0153] A porous layer (containing PVDF) with a thickness of 15 μm was prepared on the surface of the positive electrode sheet in Preparation Example 2 by electrospinning. The average pore size was 150 nm, and the diameter of the nanofibers was 600 nm. The porosity was 80%, and the air permeability when converted to 20 μm was 112 s / 100 cm 3 Then repeat the above steps on the other surface of the positive electrode sheet and dry it at 90°C to obtain a double-sided coated positive electrode sheet.
[0154] Preparation of lithium-ion batteries
[0155] The negative electrode sheet prepared in the above Preparation Example 1 and the positive electrode sheet with a separator prepared in each example are stacked opposite to each other, the four corners of the entire stacked structure are fixed with tape, and then placed in an aluminum-plastic film, top and side sealed, and the electrolyte in Preparation Example 3 is injected, and then packaged to obtain a lithium-ion stacked battery. In Example 21, the negative electrode sheet in Example 21 is used to replace the negative electrode sheet in Preparation Example 1.
[0156] Comparative Example 1
[0157] A polyethylene with a thickness of 15 μm was selected as a separator and placed between the negative electrode sheet and the positive electrode sheet of Preparation Examples 1 and 2 as a separator. The negative electrode sheet, the positive electrode sheet and the separator were stacked opposite to each other. The four corners of the entire laminate structure were fixed with tape, and then placed in an aluminum-plastic film. After the top and side seals were made, the electrolyte in the preparation example was injected, and the package was finally used to obtain a lithium-ion laminated battery.
[0158] Comparative Example 2
[0159] A PVDF non-woven fiber layer with a thickness of 15 μm was prepared on the surface of the positive electrode plate in Preparation Example 2 by electrospinning, and then a PVDF suspension was prepared, and a dense PVDF coating was prepared on the surface of the fiber layer by blade coating, and its coverage on the surface of the plate was 100%. The average pore size of the fiber layer was 50 nm and the porosity was 80%. Then, the above steps were repeated on the other surface of the positive electrode plate, and the solvent and dispersant in the coating were dried at 90°C to obtain a double-sided coated positive electrode plate.
[0160] The coated negative electrode sheet and positive electrode sheet are stacked opposite each other, the four corners of the entire stacked structure are fixed with tape, and then placed in an aluminum-plastic film. After top and side sealing, injection of the electrolyte in the preparation example, and packaging, a lithium-ion stacked battery is finally obtained.
[0161] The data and test results of each embodiment and comparative example are shown in Table 1.
[0162]
[0163]
[0164] It can be seen from Table 1 that compared with Comparative Example 1, the bonding force between the isolation layer and the negative electrode in each embodiment of the present application is significantly increased, and the ratio of the 2C discharge specific capacity to the 0.1C discharge specific capacity is significantly improved.
[0165] Compared with Comparative Example 2, the ratio of 2C discharge specific capacity to 0.1C discharge specific capacity is significantly improved, and the discharge capacity after 50 charge and discharge cycles / first discharge capacity is significantly improved, indicating that the cycle performance of the battery is significantly improved.
[0166] In addition, the isolation layer of Example 23 does not contain polymer aggregates. By comparing with other examples, it can be seen that after adding polymer aggregates, the bonding force between the isolation layer and the negative electrode is significantly increased, and the safety of the battery is improved.
[0167] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. An electrochemical device, comprising an electrode plate and a separation layer formed on the surface of the electrode plate, wherein the separation layer comprises a porous layer formed on the surface of the electrode plate; the porous layer comprises nanofibers, and the electrolyte injection property of the separation layer is less than 15 seconds; The isolation layer further comprises a polymer layer, the coverage area ratio of the polymer layer on the porous layer is 10% to 70%, the polymer layer comprises polymer aggregates, and the polymer aggregates have at least one of the following characteristics: (a) The maximum coverage area of a single polymer aggregate in the polymer layer is 1×10 -5 mm 2 ~1mm 2 ; (b) the depth of the polymer aggregates in the polymer layer embedded in the porous layer accounts for 0.01% to 80% of the thickness of the porous layer; (c) The depth of the polymer aggregates in the polymer layer embedded in the porous layer accounts for 10% to 80% of the thickness of the polymer aggregates.
2. The electrochemical device according to claim 1, wherein the maximum coverage area of a single polymer aggregate in the polymer layer is 0.001 mm 2 ~0.05mm 2 .
3. The electrochemical device of claim 1, wherein the isolation layer has at least one of the following features: (a) When the thickness of the isolation layer is converted to 20 μm, the air permeability is 5 s / 100 cm 3 ~400 s / 100cm 3 ; (b) the porosity of the isolation layer is 30% to 95%; (c) the average pore size of the porous layer is 20 nm to 10 μm; (d) The thickness of the isolation layer is 1 μm to 20 μm. The electrochemical device according to claim 1 , wherein the diameter of the nanofibers is 0.1 nm to 2 μm.
5. The electrochemical device of claim 1, wherein the nanofibers comprise at least one of polyvinylidene fluoride, polyimide, polyamide, polyacrylonitrile, polyethylene glycol, polyphenylene ether, polypropylene carbonate, polymethyl methacrylate, polyethylene terephthalate, polyethylene oxide, polyvinylidene fluoride-hexafluoropropylene, or polyvinylidene fluoride-chlorotrifluoroethylene. 6 . The electrochemical device according to claim 1 , wherein the polymer layer is disposed on the porous layer, and the thickness of the polymer layer is 0.05 mm to 4 mm. The electrochemical device according to claim 6 , wherein the polymer layer has a regular pattern. 8 . The electrochemical device according to claim 1 , wherein the separation layer further comprises an inorganic compound layer, the inorganic compound layer comprising inorganic particles, the inorganic compound layer being disposed on the porous layer.
9. The electrochemical device according to claim 8, wherein the inorganic compound layer has at least one of the following features: (a) a portion of the inorganic particles in the inorganic compound layer are embedded in the porous layer; (b) the depth of the inorganic particles of the inorganic compound layer embedded in the porous layer accounts for 0.01% to 80% of the thickness of the porous layer; (c) The electronic resistivity of the inorganic compound layer is greater than 10 7 Ω×m; (d) The ionic conductivity of the inorganic compound layer is 10 -8 S / cm~10 -2 S / cm; (e) the thickness of the inorganic compound layer is 0.1 μm to 20 μm; (f) The inorganic compound layer has a porosity of 10% to 40% and a pore size of 0.001 μm to 8 μm.
10. The electrochemical device according to claim 8, wherein the inorganic compound layer is provided by spraying or deposition.
11. The electrochemical device according to claim 8, wherein the inorganic compound layer and the porous layer are bonded by heat pressing or bonding.
12. The electrochemical device according to any one of claims 1 to 11, wherein an average pore size of the porous layer varies in a thickness direction. 13 . The electrochemical device according to claim 12 , wherein an average pore size of the porous layer closer to the electrode pad region is smaller than an average pore size of the porous layer farther from the electrode pad region.
14. The electrochemical device according to claim 1, wherein the porous layer is prepared by electrospinning, air spinning or centrifugal spinning.
15. An electronic device comprising the electrochemical device according to any one of claims 1 to 14.
Citation Information
Patent Citations
Electrochemical device
CN109802083A